Separate Aspects of Development of Confidential Collaboration Institute on the Territory of Ukraine in a Soviet Period - V. M. Davydiuk (Law and Safety)
A retrospective analysis of the organizational and legal provision of the work with confidents on the territory of modern Ukraine in the Soviet period has been carried out. Normative and legal regulation of the work with confidents during the reign of various Soviet leaders has been outlined. The experimental approaches in the work with secret apparatus, which were used in the 20s of the XX century in the Soviet state, have been revealed. The provision of the principle of offensive and conspiracy in the work of the agents of that time has been outlined. Some organizational and tactical methods of the work with confidents in different years have been revealed, their common and distinctive features have been singled out. The classification of secret apparatus by the categories in different periods of time has been provided. The serious influence of the personalities of the leaders of the Soviet state on the development of the system of secret work in general and the work with confidents, in particular, has been noted. The author has emphasized on the normative and methodological basis of the work with confidents during Stalinist times against the opponents of the regime; the author has noted the wide use of political search. The mechanism of ensuring safety of confidents has been revealed. The peculiarities of the work with confidents in the thaw and standstill periods have been studied. The disadvantages and advantages of the work with secret apparatus during certain time intervals have been outlined. The influence of the development of the science of operative and search activity on the system of secret work and its agent component has been also outlined.